Kinetics of Muscle Carnosine Decay after β-Alanine Supplementation: A 16-wk Washout Study - YAMAGUCHI, GUILHERME CARVALHO (Med Sci Sports Exerc, 2021)
PURPOSE: This study aimed to describe the kinetics of carnosine washout in human skeletal muscle over 16 wk. METHODS: Carnosine washout kinetics were studied in 15 young, physically active omnivorous men randomly assigned to take 6.4 g·d(−1) of β-alanine (n = 11) or placebo (n = 4) for 8 wk. Muscle carnosine content (M-Carn) was determined before (PRE), immediately after (POST), and 4, 8, 12, and 16 wk after supplementation. High-intensity exercise tests were performed at these same time points. Linear and exponential models were fitted to the washout data, and the leave-one-out method was used to select the model with the best fit for M-Carn decay data. Repeated-measures correlation analysis was used to assess the association between changes in M-Carn and changes in performance. RESULTS: M-Carn increased from PRE to POST in the β-alanine group only (+91.1% ± 29.1%; placebo, +0.04% ± 10.1%; P < 0.0001). M-Carn started to decrease after cessation of β-alanine supplementation and continued to decrease until week 16 (POST4, +59% ± 40%; POST8, +35% ± 39%; POST12, +18% ± 32%; POST16, −3% ± 24% of PRE M-Carn). From week 12 onward, M-Carn was no longer statistically different from PRE. Both linear and exponential models displayed very similar fit and could be used to describe carnosine washout, although the linear model presented a slightly better fit. The decay in M-Carn was mirrored by a similar decay in high-intensity exercise tolerance; M-Carn was moderately and significantly correlated with total mechanical work done (r = 0.505; P = 0.032) and time to exhaustion (r = 0.72; P < 0.001). CONCLUSIONS: Carnosine washout takes 12–16 wk to complete, and it can be described either by linear or exponential curves. Changes in M-Carn seem to be mirrored by changes in high-intensity exercise tolerance. This information can be used to optimize β-alanine supplementation strategies.